Thermal contact conductance of various metal interfaces at cryogenic temperature. (3rd January 2020) - Kim, Myung Su; Seo, Young Ho; Choi, Yeon Suk
A pressed joint by screw bolts is widely used in many cryogenic applications like superconducting magnet system, cryogenic storage vessel, as well as engineering application such as semiconductor device, aerospace structure manufacturing. Therefore, accurate measurement and analysis of thermal contact conductance (TCC) at low temperature should be done. Changes in TCC are related to many variables such as surface condition, contact pressure, material and mechanical strength. In this study, TCC measurement was performed with variables of material and temperature. Three metal materials (copper, stainless steel and brass), which are mainly used for heat transferring were selected as specimens considering the mechanical and thermal properties. The steady state method was adopted for measuring of TCC and the cryocooler and electrical heater were used to control the temperature. A specimen with surface roughness of about 0.2 um (Ra) was prepared and TCC was measured at 7 MPa contact pressure and in the temperature range of 6-220 K. The results of TCC measurement with respect to the material, operating temperature and contact pressure are discussed. In addition, the relation between TCC and surface deformation of specimen is also investigated.